Japanese policy on islam and malay-muslim community during its occupation of Malaya, 1941-1945 - Mansor Majdin, Mohamad Firdaus; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2017)
Japanese occupation of Malaya is considered to be a departure point in Malaysia’s history which marked a shift of a new colonial master from British to Japanese. In the context of Malaya, following the successful Japanese subjugation of the land in February 1942, the High Command in Tokyo had issued a number of directives to be implemented in the occupied areas including Malaya. The High Command in Tokyo, among others had specified that regional commanders need to respect the natives’ religion and folk customs in the occupied areas. As far as Islam is concerned, the Japanese Military Administration seemed to depart from Tokyo’s orders in its dealing with Islam and Malay-Muslims as a whole.